TECHNOLOGY FOR WATER PURIFICATION FROM RESIDUES OF DRUGS AND PLASTIC - Dolina, L. F.; Mashykhina, P. B.; Dolina, D. A. (Science and Transport Progress, 2019)
Purpose. The main purpose of the article is to develop a technology for water purification from residues of oil-fat containing drug (medicinal) cream, in particular technology and a technological scheme for purifying urban (municipal) wastewater from plastics and residues of drugs. Methodology. The studies were carried out based on the analysis of scientific sources and reporting data on the availability of drugs and plastics in the water of Ukraine, European countries, and the USA. Findings. The authors present the results of a comprehensive review of issues related to the determination of the availability of drugs in various waters, their concentrations and the most dangerous drugs-toxicants. Medicines and plastics can accumulate not only in humans and animals, but also in sea and river fish, etc. The presence of drugs and plastic in the body can have a negative impact on the health. The treatment facilities in Ukraine and the world are not sufficiently adapted for the detection of drugs and plastics and their purification. Originality. The authors of this material conducted studies to determine the content of plastic in drinking tap water in Dnipro and Zaporizhzhia cities. Drinking water from the tap contains less plastic particles than bottled water of the famous Ukrainian trade brands. The work developed technological schemes for the purification of industrial wastewater from pharmaceutical enterprises for the manufacture of creams, ointments, oils and other products for treatment and cosmetic purposes. Structures and methods for purifying water from these pollutants have been proposed, which had not been previously used at water purification stations, but successfully apply in other industries. Practical value. The use of environmentally efficient technologies in Ukraine will allow obtaining high-quality drinking water, but it will require re-equipment and reconstruction of water treatment plants. Major funding should be provided by corresponding articles. Currently, in Ukraine (even in Kyiv) there are no stations for the purification of drinking and waste waters, which would use modern technologies and facilities, but high-quality water is the health and life of people.